2018
DOI: 10.1002/cam4.1618
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of circulating pro‐angiogenic miRNAs’ expressions with disease risk, clinicopathological features, and survival profiles in gastric cancer

Abstract: This study aimed to explore the correlation of circulating pro‐angiogenic miRNAs’ expressions with risk, clinicopathological features, and survival profiles in gastric cancer (GC). Three hundred and thirty‐three GC patients underwent radical resection and 117 health controls (HCs) were recruited for this study. Plasma samples were obtained from GC patients before the operation and from HCs after enrollment. Fourteen pro‐angiogenic miRNAs were asseassed by quantitative polymerase chain reaction (qPCR). Disease‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…The oncogene MYC induces the miR-17 family, which in turn dysregulates cell cycle progression, apoptosis, and tumor invasion via interactions with PTEN [25], E2F genes [26], and the transforming growth factor beta (TGF-β) pathway [27]. miR-20a has been shown to be upregulated across both solid and hematopoietic cancers [28] and has even been suggested as a diagnostic serum biomarker for gastric [29], nasopharyngeal [30], and prostate cancer [31]. However, miR-20a has been particularly noted for its regulatory role in CRC by upregulating the TGF-β signaling cascade.…”
Section: Introductionmentioning
confidence: 99%
“…The oncogene MYC induces the miR-17 family, which in turn dysregulates cell cycle progression, apoptosis, and tumor invasion via interactions with PTEN [25], E2F genes [26], and the transforming growth factor beta (TGF-β) pathway [27]. miR-20a has been shown to be upregulated across both solid and hematopoietic cancers [28] and has even been suggested as a diagnostic serum biomarker for gastric [29], nasopharyngeal [30], and prostate cancer [31]. However, miR-20a has been particularly noted for its regulatory role in CRC by upregulating the TGF-β signaling cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have explored that a poor prognosis of cancer patients comes with an upregulated expression of miR-92a in tumor tissues or blood. There are a number of studies reporting that patients with a high expression level of miR-92a experience a low survival rates or quick tumor progression and metastasis in colorectal cancer20-23, non-small cell lung cancer24, 25, osteosarcoma26, 27, hepatocellular carcinoma28, 29, gastric cancer30-32, esophageal squamous cell carcinoma33, multiple myeloma34, non-muscle invasive bladder cancers35 and nasopharyngeal carcinoma36. Nevertheless, some emerging studies have identified that an increased miR-92a level was closely linked to a favorable survival: Nilsson et al37 pointed out that upregulation of miR-92a was associated with decreased tumor macrophage infiltration and better outcomes in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen articles were further removed because no survival analysis results were reported and insufficient survival data were available to recalculate HR and 95% CI. Finally, 24 eligible articles (27 studies) [11, 1418, 2126, 30, 31, 4453] including 12 articles [11, 1418, 21, 44–48] for miRNA-130a and 12 articles (15 studies) [2226, 30, 31, 4953] for miRNA-130b were included in this meta-analysis. Three articles [23, 49, 52] included two cohort studies from different populations (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The potential mechanisms may involved down-regulation of tumor suppressor gene, phosphatase and tensin homolog ( PTEN ) in osteosarcoma and breast cancer [11, 12], runt-related transcription factor 3 ( RUNX - 3 ) and collapsing-response mediator protein type 4 ( CRMP4 ) in gastric cancer [10, 17], peroxisome proliferator-activated receptor gamma ( PPARG ) in chorangiocarcinoma [16] and enhanced mammalian target of rapamycin (mTOR) signaling pathway in ovarian cancer [13]. However, a retrospective analysis showed that miRNA-130a had no significant effect on the prognosis of gastric cancer [18]. Moreover, miRNA-130a, acted like a tumor suppressor, has been reported to inhibit the androgen receptor (AR) and mitogen activated protein kinase (MAPK) pathways and target FOS-like antigen 1 ( FOSL1 ) in prostate cancer [19], and triple-negative breast cancer [20], respectively.…”
Section: Introductionmentioning
confidence: 99%